Knowledge, attitude and practice of influenza vaccination among adults attending Pusat Kesihatan Universiti (PKU) UPM - Mohd Taib, N.; Mohd Mundir, E.M.; Abdul Manan Ponan, S.N.A.; Kuay, H.Y.; Masri, S.N.; Tengku Jamaluddin, T.Z.M. (Elsevier, 2020)
Background: Influenza is a contagious respiratory illness caused by influenza viruses which range from mild to severe illness. It is one of the leading causes of communicable disease in Malaysia. Despite awareness campaigns regarding the disease and its prevention, the vaccination rates are still low. This study aimed to evaluate knowledge, attitude and practice levels among attendees at Pusat Kesihatan Universiti (PKU) UPM. Methods and materials: A cross-sectional study was conducted among adults in Pusat Kesihatan Universiti (PKU) UPM. Attendees to PKU were randomly sampled and were required to fill in a self-administered questionnaire. Data was analysed by IBM Statistical package for Social Science (SPSS) Version 25. Chi-square bivariate analysis were used to measure the association between the variables. Results: A total of 235 adults participated in this study. Most respondents were female (n = 147, 62.6%), within the age group 18-29 years old (n = 144, 61.3%), Malays (n = 194, 82.6%) and Muslim (n = 196,83.4%). The study revealed respondents had good knowledge (n = 181, 77.0%), good attitude (n = 163, 69.4%) but poor practice (n = 105, 44.7%) towards influenza and vaccination. More than 80% had correct knowledge regarding influenza and the severity of the disease, availability of influenza vaccine, effectiveness of influenza vaccine against the disease and the risk of non-vaccinated. There is a significant association between knowledge towards attitude regarding influenza and vaccination (p < 0.05). There is no significant association between knowledge towards practice regarding influenza and vaccination (p > 0.05). However, there is a significant association between attitude towards practice regarding influenza vaccination (p < 0.05). Conclusion: These results indicate good knowledge influences attitude towards influenza vaccination and good attitude influences practice towards influenza vaccination. The uptake of influenza vaccine in this study was not influenced directly by the level of knowledge. Attitude modification towards influenza vaccination is necessary to improve the vaccine uptake.